Cultural Criticism between Analysis and Interpretation: A Review of the Book (Critique of Cultural Criticism) by Dr. Abdel Azim Al-Sultani - Prof. Dr. Jassim Hussein Al-Khaldi (Journal of College of Education, 2025)
In his book Critique of Cultural Criticism: A Vision for Questioning Concepts and Cognitive Regulation, Dr. Abdul Azim Al-Sultani explores the issue of terminology within the field of cultural criticism, beginning with the notion of culture as an essential aspect of human existence and a means of engaging with life.Al-Sultani examines the confusion between cultural studies and cultural criticism, tracing its historical roots to the nineteenth century with Matthew Arnold.He highlights the foundational contributions of figures such as Roland Barthes in Mythologies, who broadened the concept of the cultural text, and Raymond Williams in Culture and Society, who examined the manifestations of cultural decline.Ultimately, Al-Sultani advocates for the critical interrogation and cognitive regulation of concepts to foster a more conscious and methodical practice of cultural criticism.
Keywords: Cultural Criticism, Analysis and Interpretation, Critique of Critique, Abd al-Azim al-Sultani, Examination of Concepts